2013
DOI: 10.1192/bjp.bp.112.113506
|View full text |Cite
|
Sign up to set email alerts
|

Attempted suicide v. non-suicidal self-injury: behaviour, syndrome or diagnosis?

Abstract: Nomenclature used to describe acts of self-harm without fatal consequences varies considerably. The term 'non-suicidal self-injury' (NSSI) offers an opportunity to clarify study in this field, dichotomising the presence or absence of suicidal intent. This may improve consistency in reporting suicide and self-injurious behaviour with implications for management and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 10 publications
(17 reference statements)
1
58
0
1
Order By: Relevance
“…As we have discussed, similar proposals have been made concerning studies of self-injury, given recent research that has shown that NSSI cuts across many mental disorders as they have been traditionally defined (e.g., Selby et al, 2012;Shaffer & Jacobson, 2009). Although the inclusion of NSSI disorder as a condition in need of further study in the DSM-5 represents increasing recognition of NSSI as a transdiagnostic phenomenon, whether NSSI is best conceptualized as a formal diagnosis, symptom, or behavior is still subject to debate (e.g., Butler & Malone, 2013). Studies in which researchers have used and tested the NSSI disorder criteria are emerging in the literature, and preliminary results are promising (e.g., Selby et al, 2012;Zetterqvist, Lundh, Dahlström, & Svedin, 2013); however, continued research in this area will undoubtedly help determine the ideal classification for this prevalent phenomenon.…”
Section: Question 7: Can Self-injury Studies Be Prioritized In Currenmentioning
confidence: 99%
“…As we have discussed, similar proposals have been made concerning studies of self-injury, given recent research that has shown that NSSI cuts across many mental disorders as they have been traditionally defined (e.g., Selby et al, 2012;Shaffer & Jacobson, 2009). Although the inclusion of NSSI disorder as a condition in need of further study in the DSM-5 represents increasing recognition of NSSI as a transdiagnostic phenomenon, whether NSSI is best conceptualized as a formal diagnosis, symptom, or behavior is still subject to debate (e.g., Butler & Malone, 2013). Studies in which researchers have used and tested the NSSI disorder criteria are emerging in the literature, and preliminary results are promising (e.g., Selby et al, 2012;Zetterqvist, Lundh, Dahlström, & Svedin, 2013); however, continued research in this area will undoubtedly help determine the ideal classification for this prevalent phenomenon.…”
Section: Question 7: Can Self-injury Studies Be Prioritized In Currenmentioning
confidence: 99%
“…Although NSSI and SA share similarities in their risk factors (Andover et al, 2012), and a history of NSSI increases risk for suicide (Claes et al, 2010b), these two behaviors are distinct from each other in a number of ways. Namely, whereas NSSI represents a maladaptive coping mechanism to regulate emotions, a suicide attempt reflects a desire to end one's life (Butler et al, 2013). Hence, the intention to die is the most basic distinction between these behaviors (Andover et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is a debate about the relationship between NSSI and suicidal self-injury, with some researchers highlighting both behaviours are distinct 17 , whereas others are more cautious in clearly differentiating these two behaviours 18 . Numerous studies have noted that non-suicidal and suicidal self-injurious behaviours co-occur frequently 14,19,20 and that NSSI longitudinally predicts increased risk of suicidal behaviours 2123 .…”
mentioning
confidence: 99%